Yahoo Web Search

  1. Sort by

  1. ...)/ (x^2+1)^2 Then multiply all terms by the denominator of the LHS, and equate coefficients for each separate power of x. I admit this...

    2 Answers · Science & Mathematics · 23/12/2013

  2. ...the ODE becomes x^2 y^4 dx + 2x^3 y^3 dy = 0, but this time, the LHS isn't an exact differential, so this expression (x^2 y^3) didn't turn out to be...

    1 Answers · Science & Mathematics · 03/12/2013

  3. ... obvious, just divide RHS by the bracketed coefficient from the LHS.

    1 Answers · Science & Mathematics · 25/11/2013

  4. ...: tan² θ cos² θ + cot² θ sin²θ = 1 LHS = (sin²θ/cos²θ) × cos² θ+ (cos²θ/sinθ²...

    1 Answers · Science & Mathematics · 01/10/2013

  5. ...u+1)/u u du/(u+1) = dx Now it's separated; to integrate the LHS, let v=u+1, so (1 - 1/v) dv = dx v - ln|v| = x + C1 u - ln|u+1| = x + ...

    2 Answers · Science & Mathematics · 02/10/2013

  6. LHS: F=m.a =kg. m/s2 =ML/T2 RHS: rho=kg/m3 g =m/s2 V=m3 Multiplying these, F=kg.m/s2 =ML/T2 Thus, RHS=LHS Hence the proof!

    1 Answers · Science & Mathematics · 03/09/2013

  7. ...of the RHS is obviously ln(x) + C. Integral of the LHS looks tough, trying Wolfram Integrator if you'...

    1 Answers · Science & Mathematics · 02/07/2013

  8. ...91 is a transformation of Eqn 2-88, using 2-89 to replace the LHS and using 2.90 to replace the RHS of 2-88. Eqn 2-92 ...

    1 Answers · Science & Mathematics · 26/05/2013

  9. ...x) - cos(x)/sin(x) = tan(x) - cot(x) But now it's perfectly clear that the LHS equals the RHS.

    1 Answers · Science & Mathematics · 23/04/2013

  10. ... should check this back to see that it satisfies the differential equation (LHS) but no time I'm afraid! We now have to find any particular solution...

    2 Answers · Science & Mathematics · 19/03/2013

  1. Try asking your question on Yahoo Answers